Adherence to diabetic retinopathy screening among children and young adults in Bangladesh - Katie Curran; Munir Ahmed; Mirza Manbira Sultana; Salissou Moutari; Mohammad Awlad Hossain; Laura Cushley; Tunde Peto; Lutful Husain; Bedowra Zabeen; Nathan Congdon (Clinical Diabetes and Endocrinology)
Abstract Background Effective diabetic retinopathy screening (DRS) programmes are important in preventing vision impairment and blindness caused by diabetes. This study focuses on identifying the factors affecting attendance or non-adherence to DRS among children and young adults with diabetes mellitus (DM) in Bangladesh. Methods A mixed-methods approach was used, which included patients diagnosed with DM aged 12–26 years from Bangladesh who were registered at BIRDEM Women and Children hospital in Dhaka. Data collection occurred between July 2019 and July 2020, mainly through telephone and email due to restrictions imposed by the COVID-19 pandemic. Statistical analyses, including chi-squared tests, t-tests, and logistic regression, were used to assess the demographic and clinical factors influencing attendance at DRS. Results The study reported a high 88% attendance rate for DRS among children and young adults in Bangladesh. However, some barriers to attendance were identified. Children under 15 years of age showed a higher tendency to attend their last DRS appointment when compared to older age participants (16–26 years), P < 0.05. Male participants demonstrated a lower likelihood of attending their DRS appointments than females (OR 0.29, CI: 0.17 to 0.50), P < 0.001. Additionally, participants with higher HbA1c levels (mean 9.1%, IQR 2.5) attended their last DRS appointment compared to those with lower levels (mean 8.0%) (p < 0.05). The primary barriers leading to missed DRS appointments were distance to the hospital (15, 31.9%), financial limitations (19, 40.4%), and busy schedules (14, 29.8%). Conclusions Compliance with DRS was high in this setting especially among younger patients, females, and those with higher HbA1c levels, highlighting the effectiveness of current DRS initiatives in Bangladesh. Addressing barriers such as cost, service accessibility and transportation could improve attendance rates further, and strategies such as flexible scheduling, transport subsidies, telemedicine, and use of artificial intelligence may help overcome these challenges.